Effect of Mobile Phone Base Stations on Antioxidant and Oxidant Serum Levels: Possible Impact on Cancer Development - Ali Hadhod, Sara; Noory Fajer, Ali (Asian Pacific Journal of Cancer Biology, 2024)
Background: There have been claims of a potential link between radio frequency (RF) emissions from mobile phone stations and cancer. In addition, widespread public concern has been expressed about the placement of cell phone antennas due to concerns about the risk of cancer. Objective: The objective of the study was to assess the effect of mobile phone base stations on oxidant and antioxidant markers and to investigate its potential correlation with cancer progression. Methods: The study involved three groups: cancer patients, healthy individuals residing near mobile phone base stations, and a control group living away from such base stations. Results: The study revealed significant differences in most biochemical parameters among the groups, highlighting the impact of mobile phone base stations on health. Cancer patients residing near mobile phone base stations (Group 1) showed notable changes compared to healthy individuals living both near (Group 2) and far (Group 3, control group) from mobile phone base stations. Specifically, the harmful effects of mobile phone base stations were evident in the increased total oxidant status (TOS), decreased total antioxidant capacity (T-AOC), and altered liver enzymatic activities (AST, ALP, ALT, LDH). Conclusion: This study finding suggests that proximity to mobile phone base stations may negatively influence oxidative stress and liver function leading to cancer. Further research is necessary to fully understand these effects and develop appropriate public health strategies.